KEHIDUPAN MASYARAKAT JEPANG PADA MASA PERANG DUNIA II DALAM NOVEL JAPANESE ROSE KARYA KIMURA REI ( - MAULIDA, SARAH (Jurnal Ilmiah Mahasiswa FIB, 2013)
Japanese Rose is a novel by Kimura Rei. The novel is first published in 2009. Japanese Rose tells an untold story of “kamikaze” pilot in Japanese history. This novel is also telling a story about how difficult it is the lives of Japanese people when the World War II happened.The writer used sociology in literature approach to help the writer analyzing the novel. Sociology in literature is an approach centered in the study of society, through institutions occurred in society like family, economy, politic, religion, and education.There are similarities between social realities with the story of the novel. Novel is a literature made based on the community. These following results are found in a research: Family institution is divided because of statutory military service. Economy institution experienced difficulties getting daily-needed because of embargo. Politic institution became arrogance and authoritarian creating patriotism propaganda to affect people’s mind. In religious institution, Shinto controlled Japanese people to make them obedient to the emperor. Educative institution in this novel became harsher and forcing young men to join statutory military service, and put the women as nurses of the war’s victimsIn addition, it’s recommended for next research to use the Japanese Rose novel with different approach, for example to research the affection of “Hakko Ichiu” doctrine in Japan involvement at World War II that is filled in the novel. The purpose is to increase our appreciation in literatures. Keywords : Japanese Rose, novel, sociology in literature, the life of Japanese people, World War II